Evaluation of healing in partial skin graft donor sites using a xenograft compared to a synthetic cellulose skin substitute - Chau Ramos, Enrique Antonio (2019)
Objective: To evaluate healing in partial skin graft donor sites using a skin substitute compared to a xenograft in patients with different diseases requiring partial skin grafting. Materials and methods: This paper presents a report of 20 patients between 19 and 65 years from the Plastic Surgery Unit of the Hospital María Auxiliadora in Lima Metropolitan Area, Peru, between December 2017 and June 2018, where healing was evaluated in partial skin graft donor sites. An interventional, analytical, prospective and longitudinal study was conducted using a double-blind design to control possible biases. For the statistical significance analysis, nonparametric tests with a 95 % confidence interval were used. Results: Using a skin substitute, a better healing quality of donor sites of epithelialization was seen compared with xenografting. Both techniques were evaluated with the Vancouver scale, which considers five aspects (healing, vascularity, pigmentation, flexibility and height), out of which healing showed significant results (p<0.05). Estimation of the risk in the healing process according to the Cox proportional hazards model showed that H = 0.60 (95 % CI 0.46- 0.78), which indicates that the shortest healing time was found in the skin substitute group. Conclusions: Skin substitutes are an important alternative that favors the good quality of healing in donor sites. skin substitutes proved to be more effective than conventional xenografting when evaluated and compared using the Vancouver healing scale.